1982 uncovered : the Falklands War Mapping Project - Clack, Timothy,; Pollard, Tony, (Archaeopress Archaeology, 2022)
War and its legacy are traumatic to individuals, communities, and landscapes. The impacts last long beyond the events themselves and shape lives and generations. Archaeology has a part to play in the recording of, and recovery from, such trauma. This volume delivers the first intensive archaeological survey of the battlefields of the Falklands War.